Self-assembled ferritin nanoparticles displaying PcrV and OprI as an adjuvant-free Pseudomonas aeruginosa vaccine - Li, Yuhang; Pu, Ruixue; Zhang, Yi; Zhang, Yiwen; Wei, Yujie; Zeng, Sheng; Gao, Chen; Wang, Ying; Yin, Daijiajia; Zhang, Yueyue; Wan, Jiqing; Zou, Quanming; et al. (Frontiers in Immunology, 2023)
Serious infections of Pseudomonas aeruginosa (PA) in hospitals and the emergence and increase of multidrug resistance have raised an urgent need for effective vaccines. However, no vaccine has been approved to date. One possible reason for this is the limited immune response due to the lack of an efficient delivery system. Self-assembled ferritin nanoparticles are good carriers of heterogeneous antigens, which enhance the activation of immunological responses. In this study, two well-studied antigen candidates, PcrV and OprI, were selected and connected to the ferritin nanoparticle by the Spytag/SpyCatcher system to generate the nanovaccine rePO-FN. Compared to recombinant PcrV-OprI formulated with aluminum adjuvants, intramuscular immunization with adjuvant-free rePO-FN induced quick and efficient immunity and conferred protection against PA pneumonia in mice. In addition, intranasal immunization with adjuvant-free rePO-FN enhanced protective mucosal immunity. Moreover, rePO-FN exhibited good biocompatibility and safety. Our results suggest that rePO-FN is a promising vaccine candidate, as well as, provide additional evidence for the success of ferritin-based nanovaccines.